The importance of customization on the acceptance of the enterprise resource planning (ERP) system in Chinese company - Wang, Xu (online, 2016)
ERP systems have been widely studied during the past decades, yet they often fail to deliver the intended benefits originally expected. One notable reason is the lack of understanding how the customization influence the ERP user acceptance when there is lack of system-to-business fit, which can lead to negative business outcomes. For some reasons, many have argued that a vanilla
Dissertation, Université Grenoble Alpes, 2016
Keywords: Graue Literatur; Hochschulschrift; PLS-SEM; Misfit; Adaptation; Enhancement; ERP; Customization